PENERAPAN TEKNOLOGI PENGOLAHAN LIMBAH KELAPA SEBAGAI PUPUK ORGANIK DAN NATA DE COCO - Darma Bakti; Ridwansyah; Isman Nuriadi (Talenta Publisher, 2018)
Community service activities is one of the obligations that must be implemented by lecturer at the university sabagai one aspect of Tri Dharma Perguruan Tinggi. The activity was carried out by a Team of Community Service entitled